Predictors Of The Development Of Chronic Kidney Disease In Patients With Chronic Obstructive Pulmonary Disease - Kayumova Gulnoz Karimovna; Akhmedova Nilufar Sharipovna; Umurova Nigora Mavlyanovna (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
The aim of the study was to identify predictors of decreased glomerular filtration in patients with chronic obstructive pulmonary disease (COPD). Materials and methods. We analyzed 145 case histories of patients diagnosed with COPD. The majority (84.1%, n = 122) of them are males (the average age of men is 60.7 ± 0.9 years, the average age of women is 62.0 ± 2.7 years). A comparative analysis of the prevalence of risk factors for chronic kidney disease (CKD) in patients with COPD: age, gender, smoking, arterial hypertension, overweight, etc. The glomerular filtration rate (GFR) was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD – EPI) formula, according to which the patients were divided into 6 groups: group 1 - hyperfiltration, group 2 - GFR CKD – EPI ≥ 90 ml / min / 1 , 73 m2, 3rd - GFR CKD – EPI 60–89 ml / min / 1.73 m2, 4th - GFR CKD – EPI 45–59 ml / min / 1.73 m2, 5th - GFR CKD – EPI 30 - 44 ml / min / 1.73 m2 and 6th-GFR CKD-EPI <30 ml / min / 1.73 m2. Results. Patients with COPD have a high incidence of CKD risk factors. A correlation was found between the prevalence of CKD risk factors and the severity of COPD. The main predictors of the development of CKD in patients with COPD: duration of COPD> 9 years, body mass index> 26.5 kg / m2, smoking index> 51.3, albumin> 44.0 g / l, total protein> 70.0 g / L, forced expiratory volume in the first second ≤ 1.6 L, right atrial size> 35.5 mm, systolic pressure in the pulmonary artery> 36.6 mm Hg. Art., the thickness of the posterior wall of the left ventricle> 10.5 mm, Tiffno's index ≤ 62%. Conclusion. It was found that patients with COPD